PENGARUH TEKNIK RELAKSASI BENSON TERHADAP TEKANAN DARAH LANSIA DENGAN HIPERTENSI - Novia Ervadanti; Arneliwati Arneliwati; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Increasing the elderly population every year raises a variety of health problems, one of the most trending case in elderly is hypertension. Non-pharmacology treatment chosen as an independent nursing intervention that can be done by the elderly is Benson relaxation. The aim of this study was to determine the influence of Benson relaxation on blood pressure in elderly with hypertension. The research used quasy experiment design with nonequivalent control group. The study was conducted on elderly people with hypertension in the work area of Posyandu Rintis, Fifty City Pekanbaru Health Center. The sample was chosen using a purposive sampling method that met the inclusion criteria. The amount of respondents was 30 people that divided into two groups, 15 people in the experimental group and 15 people in the group. The data analysis used was univariate analysis and bivariate analysis using the dependent t test and independent t test. The instrument of this study using digital tensimeter. The statistical test results obtained p value posttest of systolic blood pressure on experimental group was (0,000) < α (0,05) and diastolic blood pressure on experimental group was (0,000) < α (0,05), so it was found that there was a decrease in blood pressure in elderly with hypertension in the work area of the Posyandu Rintis. This Benson relaxation therapy can be applied as one of the nonpharmacological independent nursing interventions to overcome hypertension problems in the elderly. Keywords: Benson relaxation, elderly, hypertension